Pedicled, vascularized occipital bone graft to supplement atlantoaxial arthrodesis for the treatment of pseudoarthrosis. (April 2020) - Reece, Edward M.; Vedantam, Aditya; Lee, Sungho; Bhadkamkar, Mohin; Kaufman, Matthew; Bohl, Michael A.; Chang, Steve W.; Porter, Randall W.; Theodore, Nicholas; Kakarla, U. Kumar; Ropper, Alexander E.
Highlights: Harvesting an occipital bone graft with a muscular pedicle is a feasible treatment for atlanto-axial pseudoarthrosis. This technique leverages the advantages of vascularized autograft without the complexities of free-tissue grafting. Variations of this technique may be useful for vascularized bone grafting in other regions of the spine. Abstract: Atlantoaxial pseudoarthrosis is a challenging postoperative complication. The use of a local, vascularized bone graft, without free tissue transfer, to support a revision atlantoaxial fusion has not been previously described. We report the first surgical patient who received a semispinalis capitis muscle pedicled, occipital bone graft for supplementation of a revision atlantoaxial arthrodesis . A 72-year-old female had a failed atlantoaxial fusion and developed neck pain from continued instability and fractured hardware. The fixation and fusion were revised and supplemented with a novel, pedicled occipital bone graft. A craniectomy was performed in the occipital bone while still attached to the semispinalis capitis muscle to provide graft vascularity. This graft was rotated inferiorly from the skull base to the C1 arch and C2 spinous process in order to supplement a revision atlantoaxial arthrodesis. The patient had excellent clinical recovery over 18-month clinical follow up. The bone graft harvesting and rotation were performed safely and without complication. The 6-month postoperative CT scan showed partial fusion into the graft. This novel surgical technique leverages the advantages of vascularized structural autograft without adding extensive time or morbidity to the procedure as observed in free-tissue transfers. It is a safe and useful salvage technique to supplement revision atlantoaxial fusion surgeries.